Generation of a rod-specific NRL reporter line in human pluripotent stem cells - M. Joseph Phillips (Nature Portfolio, 2018)
Abstract Reporter lines generated in human pluripotent stem cells can be highly useful for the analysis of specific cell types and lineages in live cultures. We created the first human rod reporter line using CRISPR/Cas9 genome editing to replace one allele of the Neural Retina Leucine zipper (NRL) gene with an eGFP transgene in the WA09 human embryonic stem cell (hESC) line. After confirming successful targeting, three-dimensional optic vesicle structures were produced to examine reporter specificity and to track rod differentiation in culture. The NRL +/eGFP hESC line robustly and exclusively labeled the entirety of rods throughout differentiation, eventually revealing highly mature structural features. This line provides a valuable tool for studying human rod development and disease and testing therapeutic strategies for retinitis pigmentosa.